2023
DOI: 10.1002/hsr2.1071
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of COVID‐19 vaccine side effects and its associated factors among the vaccinated population of Pakistan: A cross‐sectional study

Abstract: Background Coronavirus disease 2019 (COVID‐19) vaccine side effects have an important role in the hesitancy of the general population toward vaccine administration. Therefore, this study was conducted to document the COVID‐19 vaccine side effects in our population. Materials and Methods An online survey‐based, cross‐sectional study was carried out from September 1, 2021, to October 1, 2021, to document the side effects of the COVID‐19 vaccine among the general public. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The first dosage of the vaccine was associated with a higher likelihood of side effects than the second dose. Comorbidities and prior COVID-19 infection were shown to be independent (p = 0.707) of the prevalence of adverse effects [23]. This conclusion was equivalent to another study performed in Saudi Arabia; conversely, UK research by Cristina et al presenteda low incidence of injection site pain [24,25].Likewise, these findings were similar to those of the present study and revealed that side effects were more pronounced in children than in adult participants.…”
Section: Discussionsupporting
confidence: 91%
“…The first dosage of the vaccine was associated with a higher likelihood of side effects than the second dose. Comorbidities and prior COVID-19 infection were shown to be independent (p = 0.707) of the prevalence of adverse effects [23]. This conclusion was equivalent to another study performed in Saudi Arabia; conversely, UK research by Cristina et al presenteda low incidence of injection site pain [24,25].Likewise, these findings were similar to those of the present study and revealed that side effects were more pronounced in children than in adult participants.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, for both cohorts, the most frequently reported local solicited ADR following both the first vaccination cycle and the booster dose was injection site pain. As for systemic solicited ADRs, fatigue, headache, malaise, and myalgia were the most commonly reported; such findings are in line with previously published articles [ 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“… 25–27 Moreover, a number of studies evaluating the side effects of COVID−19 vaccines in Pakistan have revealed a satisfactory safety profile among vaccine recipients. 28–30 …”
Section: Discussionmentioning
confidence: 99%